Joint effect of heat and air pollution on mortality in 620 cities of 36 countries - Stafoggia, Massimo; Michelozzi, Paola; Schneider, Alexandra; Armstrong, Ben; Scortichini, Matteo; Rai, Masna; Achilleos, Souzana; Alahmad, Barrak; Analitis, Antonis; Åström, Christofer; Bell, Michelle L; Calleja, Neville; et al. (Environment international, 2023)
BACKGROUND: The epidemiological evidence on the interaction between heat and ambient air pollution on mortality is still inconsistent. OBJECTIVES: To investigate the interaction between heat and ambient air pollution on daily mortality in a large dataset of 620 cities from 36 countries. METHODS: We used daily data on all-cause mortality, air temperature, particulate matter ≤ 10 μm (PM10), PM ≤ 2.5 μm (PM2.5), nitrogen dioxide (NO2), and ozone (O3) from 620 cities in 36 countries in the period 1995-2020. We restricted the analysis to the six consecutive warmest months in each city. City-specific data were analysed with over-dispersed Poisson regression models, followed by a multilevel random-effects meta-analysis. The joint association between air temperature and air pollutants was modelled with product terms between non-linear functions for air temperature and linear functions for air pollutants. RESULTS: We analyzed 22,630,598 deaths. An increase in mean temperature from the 75th to the 99th percentile of city-specific distributions was associated with an average 8.9 % (95 % confidence interval: 7.1 %, 10.7 %) mortality increment, ranging between 5.3 % (3.8 %, 6.9 %) and 12.8 % (8.7 %, 17.0 %), when daily PM10 was equal to 10 or 90 μg/m3, respectively. Corresponding estimates when daily O3 concentrations were 40 or 160 μg/m3 were 2.9 % (1.1 %, 4.7 %) and 12.5 % (6.9 %, 18.5 %), respectively. Similarly, a 10 μg/m3 increment in PM10 was associated with a 0.54 % (0.10 %, 0.98 %) and 1.21 % (0.69 %, 1.72 %) increase in mortality when daily air temperature was set to the 1st and 99th city-specific percentiles, respectively. Corresponding mortality estimate for O3 across these temperature percentiles were 0.00 % (-0.44 %, 0.44 %) and 0.53 % (0.38 %, 0.68 %). Similar effect modification results, although slightly weaker, were found for PM2.5 and NO2. CONCLUSIONS: Suggestive evidence of effect modification between air temperature and air pollutants on mortality during the warm period was found in a global dataset of 620 cities.
Keywords: pevné částice; látky znečišťující vzduch; Air Pollution; oxid dusičitý; vystavení vlivu životního prostředí; Air Pollutants; Cities; vysoká teplota; znečištění ovzduší; Environmental Exposure; Air temperature; Effect modification; Nitrogen Dioxide; Mortality; Particulate Matter; velkoměsta; Hot Temperature; Air pollution; Epidemiology